Gender Construction in Dakwahtainment: A Case Study of Hati ke Hati Bersama Mamah Dedeh - Dicky Sofjan (Al-Jami'ah: Journal of Islamic Studies, 2012)
This case study examines the phenomenon of dakwahtainment, a concept amalgamating Islamic propagation and entertainment. It focuses on the highly popular daily live programme entitled Hati ke Hati Bersama Mamah Dedeh (literally: Heart to Heart with Mother Dedeh). The programme involves a female penceramah (preacher) providing taws}iyyah or nasehat (spiritual advice) to the jamaah (congregation), while offering religious verdicts on various aspects of life confronting Indonesian women. One of the main pillars of the programme’s success has been its tightly observed winning formula held dearly by the producer and the creative team, which stipulates 70% tuntunan (spiritual guidance) and 30% tontonan (entertainment viewing). Based on an exploratory, single case study design, research findings suggest that the Hati ke Hati Bersama Mamah Dedeh programme is constructed on a gendered understanding that is inconsistent and contradictory, which tend to simultaneously empower and disempower Muslim women viewers.[Tulisan ini merupakan studi kasus mengenai dakwahtainmen yang mempertemukan dakwah pada satu sisi dan hiburan pada sisi lainnya. Diskusi akan difokuskan pada program televisi “Hati ke Hati Bersama Mamah Dedeh.” Program ini melibatkan penceramah yang menyampaikan taws}iyyah dan nasehat yang merespon persoalan-persoalan yang kerap dihadapi perempuan Muslim di Indonesia. Salah satu kunci kesuksesan program ini adalah keberhasilan produser dan tim kreatif yang memadukan 70% tuntunan dan 30% tontonan. Tulisan ini menemukan bahwa program Hati ke Hati Bersama Mamah Dedeh dikonstruk berdasarkan pengertian relasi gender yang rancu dan saling bertentangan. Karena itu, program ini dapat memberdayakan pemirsa perempuan dan sekaligus memperlemah mereka.]